2022
DOI: 10.1002/advs.202104439
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Steep‐Slope High‐Gain MoS2 Transistors with Atomic Threshold‐Switching Gate

Abstract: The fundamental Boltzmann limitation dictates the ultimate limit of subthreshold swing (SS) to be 60 mV dec−1, which prevents the continued scaling of supply voltage. With atomically thin body, 2D semiconductors provide new possibilities for advanced low‐power electronics. Herein, ultra‐steep‐slope MoS2 resistive‐gate field‐effect transistors (RG‐FETs) by integrating atomic‐scale‐resistive filamentary with conventional MoS2 transistors, demonstrating an ultra‐low SS below 1 mV dec−1 at room temperature are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We obtain repetitive operation with low SS (32.8 mV dec −1 ) at room temperature, along with low dielectric injection efficiency (10 −6 ), through a structural design with separation of the conducting region (which determines on-state carrier transport) and the steep-switching region (where transition from off- to on-state occurs via impact ionization). Furthermore, compared to previously reported threshold switching devices using atomic filaments, 26–33 our device exhibits hysteresis-free switching characteristics because it is based on an impact ionization mechanism. The proposed I 2 S-FET overcomes the fundamental problem of dielectric degradation induced by hot carriers of impact ionization-based devices and has great potential to be extended to a monolithic steep-slope transistor array, which is considerably important in energy-efficient and high-performance electronic switches with ultra-low power loss.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We obtain repetitive operation with low SS (32.8 mV dec −1 ) at room temperature, along with low dielectric injection efficiency (10 −6 ), through a structural design with separation of the conducting region (which determines on-state carrier transport) and the steep-switching region (where transition from off- to on-state occurs via impact ionization). Furthermore, compared to previously reported threshold switching devices using atomic filaments, 26–33 our device exhibits hysteresis-free switching characteristics because it is based on an impact ionization mechanism. The proposed I 2 S-FET overcomes the fundamental problem of dielectric degradation induced by hot carriers of impact ionization-based devices and has great potential to be extended to a monolithic steep-slope transistor array, which is considerably important in energy-efficient and high-performance electronic switches with ultra-low power loss.…”
Section: Introductionmentioning
confidence: 78%
“…, separation of the main conduction device and switching transition device to achieve sub- kT / q SS) have been previously reported using atomic-filament-based threshold switches. Although low SS values of 11 mV dec −1 32 and 0.7 mV dec −1 33 have been achieved, an unacceptable level of large hysteresis (∼3 V) remains a critical challenge for these devices. In contrast, the I 2 S-FET demonstrated an insignificant level of hysteresis, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These interface disorders act as charge traps, which strongly scatter the carrier transport and degrade device performance and adversely affect the SS and hysteresis of the device. 32,35 In addition, the hysteresis loop is related to the scan rate of the gate voltage, and the faster the scan rate, the greater the hysteresis, as shown in Figure S7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Al 2 O 3 layer and channel MoS 2 have good interface characteristics. Ultrathin Al 2 O 3 as a buffer layer can prevent mutual diffusion between ferroelectric materials and channel semiconductor materials, prevent potential chemical reactions, and avoid deteriorating the surface state of semiconductor channels, effectively improving the interface quality, and thereby optimizing hysteresis. In addition, the Al 2 O 3 layer acts as a capacitor matching layer to complete the capacitance matching with the HZO negative capacitor.…”
Section: Resultsmentioning
confidence: 99%
“…Layered transition-metal dichalcogenides (TMDCs) have been attracting broad attention as materials for their wide applications in electrical devices, optical devices, and chemical sensing. TMDCs not only exhibit various electronic properties depending on their chemical composition but also can have their band gap and the conduction polarity tuned by alloying. TMDCs are expected to be a promising candidate for field-effect transistors of next-generation large-scale integrations (LSIs) that can replace silicon-based materials, since a high on/off ratio exceeding 10 7 , low subthreshold swing, and relatively high carrier mobility have been discovered even in the monolayer TMDC film. In addition to TMDCs, tin (Sn) dichalcogenides are also emerging as a good candidate for sensing applications. Previous studies have reported highly sensitive and selective SnS 2 -based sensors for detecting NO 2 and HCHO down to parts per billion levels. , Device applications of these layered materials require a method for synthesizing highly crystalline film.…”
mentioning
confidence: 99%